Iowa field reports, spring 1995, Stephen Dinsmore - Dinsmore, Stephen J.et al (1995)
An annotated list of birds sighted by Stephen Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Plustek - flatbed